Secured Data Transmission for Smart Grid System using Blockchain Technology with a Trusted Gaming Token Honeypot Algorithm - Deeptha R.; Rajeswari Mukesh; S. E. Jayanthi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The use of blockchain technology has made it possible for safe smart trade in numerous fields, including the exchange of nearby resources. Threats to the confidentiality of data recorded on the blockchain might be expected from malicious users. To combat privacy leaks in the smart grid without limiting trade capabilities, this article proposes a blockchain-based smart contract solution. Since different energy trading volumes may be mined to determine its correlations with other information like physical location and energy consumption, the proposed method primarily addresses the privacy of energy trading users in the smart grid and filters the distribution of energy sale of sellers. Finally, the keys for the encrypted data transfer were generated using the Conviction Diffie Hellman Algorithm (CDHA). Finally, the Trusted Gaming Token Honeypot Algorithm (TGTHA) was proposed to identify the untrusted user. All of the experiments were performed inside MATLAB. The efficiency of the suggested method has been experimentally verified.